The limit theorems for the sums of independent random variables - Bikelis, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бикялис. Предельные теоремы для сумм независимых случайных величинA. Bikelis. Ribinės teoremos nepriklausomų atsitiktinių dydžių sumoms